Intrinsic immunity - Cullen, Bryan R. (Current Topics in Microbiology and Immunology, 2013)
Recent research has focused attention on the importance of intrinsic antiviral immunity, i.e. immunity mediated by factors that are constitutively expressed in many cells. In this volume, leading experts provide a comprehensive overview of this relatively new and rapidly evolving field. They cover intrinsic proteinaceous antiviral immune effectors, such as the APOBEC3 and TRIM protein families as well as Tetherin and SAMHD1, which were initially discovered by researchers studying HIV-1. Furthermore, the role of RNA interference in antiviral defense in plants and invertebrates, as well as the interplay between microRNAs and viruses in mammalian cells, are analysed. One chapter discusses how intrinsic immunity and viral countermeasures to intrinsic immune effectors drive both pathogen and host evolution, and finally the emerging evidence that DNA damage response proteins restrict infection by DNA viruses is highlighted.